The development of a tool for measuring the implementation of stewardship in public health (Italian Journal of Public Health, 2012)
Background: Stewardship is contemplated as a way to make the national Health Service more efficient and effective within the context of devolution. In december 2010, the Minister of Health commissioned the university of “Sapienza" and “cattolica" of rome the task of testing and ensuring that we have the appropriate tools for evaluating the implementation level of Stewardship as part of the realization of the actions contemplated in the national Prevention Plan and their application to the Italian regions context.Methods:the method of analysis included two phases: 1) implementation of the evaluation model and assessment tool; 2) validation of the tool, with the objective of ascertaining its technical-informational functionality. the questionnaire included 141 answers in a closed format (singles or multiples) and was subdivided into five areas of analysis. every function of Stewardship was adjusted by a “weight" and a score (from 0 to 5) assigned by a panel of experts was applied to each item.Results:“ensuring accountability" was indicated as the most important Stewardship function. “ensuring accountability", “leadership", “resources Management and services", “accountability" and “evidence based medicine/evidence based prevention", respectively, characterized each function. responses were received from 75% of experts. Moreover, suggestions were collected for each question.Conclusions: considering this relatively new field of interest, to date there are no tools for looking at all aspects of stewardship. However, a rigorous instrument could be crucial for the success of policies. the proposed method could enable one to assess the level of Stewardship implementation, and to compare and propose actions for improvement. this could be essential to achieving the highest levels of quality in Public Health....
Keywords: Stewardship; Prevention; Public Health